PENINGKATAN KETERAMPILAN MENULIS KARYA SASTRA DAN PENGELOLAAN MAJALAH SASTRA BAGI MAHASISWA PROGRAM STUDI PENDIDlKAN BAHASA JA WA MELALUI MAGANG KEWlRAUSAHAAN - Suwardi, Suwardi; Widayat, Afendy (Universitas Negeri Yogyakarta, 2003)
Program of Entrepreneurship Volunteer is aimed to prepare the graduate ofJavanese Language study Program of FBS UNY Yogyakarta to compete in the job field., T,o achieve marketable graduates, the study Program offers cooperation with partners to prepare.the students in writing literary works, managing studios, and literary magazines., . , ' Process' M volunteering is perfomed by giving provisions in the partners' places.Joining students are chosen from Sanggar Sastra Lecture and selected based on talents ang motivations. The indicators of success for each student are making a title for short strory, jagading lelembut, and geguritan, and able to make a planning of studio establishment ang literary magazine.The participants were 16. However, the active persons were 11. After following.volunteering process, there were eight short stories to publish. Moreover, it is better since, there was a short story being published by mass media entitled Dak Coreng Mangsi Abang(Ari Yuliani). Of some geguritaris made by the students, almost all of them can be. published in mass media. There are 15 titles of geguritan recommended to publish, that it can be sent to mass media However, six titles need corrections. Some of the geguritans published in Sempulur magazine are Sudra, Sempati written by Agus Yuana Dirgantara and Sepi witten by Sri Suranti. Then, in the category og jagading lelembut there was seven titles and all of them are proper to publish. In other case, the effort of studio management and literary magazine establishment are still in the form of proposal consulted to the partners.Key words: written skills, literary magazine, and entrepreneurship volunteer.